2014
DOI: 10.1038/srep04545
|View full text |Cite
|
Sign up to set email alerts
|

Slow modulations of high-frequency activity (40–140 Hz) discriminate preictal changes in human focal epilepsy

Abstract: Recent evidence suggests that some seizures are preceded by preictal changes that start from minutes to hours before an ictal event. Nevertheless an adequate statistical evaluation in a large database of continuous multiday recordings is still missing. Here, we investigated the existence of preictal changes in long-term intracranial recordings from 53 patients with intractable partial epilepsy (in total 531 days and 558 clinical seizures). We describe a measure of brain excitability based on the slow modulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 56 publications
7
92
1
Order By: Relevance
“…High gamma band signal has been established as a useful index of population firing [27, 3437]. However, because of its fast oscillations, it is difficult to specify a consistent single time point for each discharge.…”
Section: Methodsmentioning
confidence: 99%
“…High gamma band signal has been established as a useful index of population firing [27, 3437]. However, because of its fast oscillations, it is difficult to specify a consistent single time point for each discharge.…”
Section: Methodsmentioning
confidence: 99%
“…The spectral power features are computationally very cost-effective, which makes them suitable candidates for implantable and portable warning systems. Furthermore, these features recently have demonstrated promising results for seizure prediction [15,35,39,[43][44][45][46], specifically in the high gamma frequency bands [15,[43][44][45][46]. Therefore, we investigated high-quality iEEG and sEEG recordings (with the sampling rates of 1024 Hz and 2500 Hz) and divided the gamma band into several narrower subbands to study the spectral behavior more precisely.…”
Section: Studied Featuresmentioning
confidence: 98%
“…Therefore, we investigated high-quality iEEG and sEEG recordings (with the sampling rates of 1024 Hz and 2500 Hz) and divided the gamma band into several narrower subbands to study the spectral behavior more precisely. Instead of using the well-known frequency bands, the subbands were selected as (0.5-4], (4)(5)(6)(7)(8), (8)(9)(10)(11)(12)(13)(14)(15), (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) The spectral powers were obtained using power spectral density (PSD) estimated through Welch's method [47]. The PSD ...…”
Section: Studied Featuresmentioning
confidence: 99%
“…In addition, increased HFOs are reported to correlate with disease severity, seizure frequency [19,21], and resection of their generators with seizure-free outcome [20,22,23 ▪ ]. In addition, recent studies have demonstrated the feasibility of seizure forecasting [24,25], and HFO show promise as a biomarker of the preictal state [26,27]. …”
Section: Introductionmentioning
confidence: 99%